The factors contributing to construction cost overruns in Perak / Muhammad Farhan Mansor and Mohamad Haszirul Mohd Hashim - Mansor, Muhammad Farhan; Mohd Hashim, Mohamad Haszirul (2023)
Cost increase has severely hit down the economy and reputations for many constructions industry around the world. Thus, this paper aims to identify and cluster the potential construction project cost increase factors. Basically, through literature review, all the potential factors that may cause cost increase were screened thoroughly before they were clustered into of the originating factors, namely project, contract, client, contractor. Meanwhile, the predominant causes of cost increase were poor preconstruction budget and material cost planning, inaccurate quantity take-off and materials cost increased by inflation. The significance of establishing the issues related to time and cost increases for the high-rise building construction project is to provide a greater insight and understanding on the causes of delays, particularly among the main project players: contractors, client, and consultants. The study identifies cost increase in construction industry and purpose of the finding to allowed recommendations to be made regarding budget management in building construction based on contractor view.The analysis of the responses reveals interesting insights regarding the impact of improper planning in construction on increasing costs. The analysis indicates that a significant majority of respondents recognize the correlation between improper planning in construction and an increasing cost.